Odontogenic myxoma: A case report and review - Das, Shreya; Mazumdar, Anjana (Indian Journal of Case Reports, 2019)
Odontogenic myxoma (OM) is a rare and locally invasive benign neoplasm that mainly affects the mandible with a peak incidence in the second–fourth decades of life and predilection for the female. The lesion often grows as a painless swelling. The radiographic features are variable, and therefore, the diagnosis is not easy. Here, we report the case of an OM in a 17-year-old-female occurred as a painless swelling in the lower right jaw for 1 month is presented. Radiologically, it showed a well-demarcated, multilocular radiolucent lesion with fine, bony trabeculae resulting in “sunburst” appearance. According to clinical and radiological features, this article represents a usual case of OM.